Pengaruh Celebrity Endorsment, Citra Merek Dan Word Of Mouth Terhadap Minat Beli Skincare “The Originote” (Studi Kasus Pada Konsumen Generasi Z) - Annisa, Balqis Firdina Nur; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract In this research the author used quantitative research methods in using primary data obtained from respondents' responses to statements in the questionnaire. The results of this research show that celebrity endorsements, word of mouth have a positive and significant effect on interest in buying "The Originote" skincare and brand image has a positive and insignificant effect on interest in buying "The Originote" skincare. The celebrity endorsement variable shows a positive influence with a sig value of 0.040, so the significance value is <0.05, which means that the better the celebrity endorsement, the higher the buying interest of "The Originote" skincare consumers. The brand image variable shows a positive influence but not significant with a sig value of 0.236, so the significance value is <0.05, which means that the better the brand image will increase buying interest in "The Originote" skincare. The word of mouth variable shows a positive influence with a sig value of 0.000, so the significance value is <0.05, which means that the better the word of mouth will increase buying interest in "The Originote" skincare. Keywords: Celebrity Endorsement, Brand Image, Word Of Mouth, Purchase Interest.